Transmedia storytelling : Pemberley Digital's adaptations of Jane Austen and Mary Shelley /: Pemberley Digital's adaptations of Jane Austen and Mary Shelley. (2018) - Camden, Jennifer; Oestreich, Kate Faber
No abstract available